In search of Amrit Kaur : a lost princess and her vanished world - Sambuy, Livia Manera, 1958- (Farrar, Straus and Giroux, 2023)
"As she builds her own life anew, an Italian writer embarks on an all-consuming search for the true story of the mysterious princess H. H. Amrit Kaur of Mandi"--